Study on the dipole moment of asphaltene molecules through dielectric measuring. (15th January 2015) - Zhang, Long-li; Yang, Chao-he; Wang, Ji-Qian; Yang, Guo-hua; Li, Li; Li, Yan Vivian; Cathles, Lawrence
Highlights: This method is capable of measuring multi dipoles in one solution simultaneously. This method can deduce dipole moment without measuring the refractive index. This method is potential to study the aggregation of asphaltenes. Abstract: The polarity of asphaltenes influences production, transportation, and refining of heavy oils. However, the dipole moment of asphaltene molecules is difficult to measure due to their complex composition and electromagnetic opaqueness. In this work, we present a convenient and efficient way to determine the dipole moment of asphaltene in solution by dielectric measurements alone without measurement of the refractive index. The dipole moment of n-heptane asphaltenes of Middle East atmospheric residue (MEAR) and Ta–He atmospheric residue (THAR) are measured within the temperature range of −60 °C to 20 °C. There is one dielectric loss peak in the measured solutions of the two types of asphaltene at the temperatures of −60 °C or −40 °C, indicating there is one type of dipole in the solution. Furthermore, there are two dielectric loss peaks in the measured solutions of the two kinds of asphaltene when the temperature rises above −5 °C, indicating there are two types of dipoles corresponding to the two peaks. This phenomenon indicates that as the temperature increases above −5 °C, the asphaltene molecules aggregate and present larger dipole moment values. The dipole moments of MEAR C7 -asphaltene aggregates are up to 5 times larger than those before aggregation. On the other hand, the dipole moments of the THAR C7 -asphaltene aggregates are only 3 times larger than those before aggregation. It will be demonstrated that this method is capable of simultaneously measuring multi dipoles in one solution, instead of obtaining only the mean dipole moment. In addition, this method can be used with a wide range of concentrations and temperatures.